ACTUALIZATION OF WOMEN IN DOMESTIC AREAS IN THE GALUH FILM - Aryawaningrat, I Gusti Ayu Agung; Santosa, Hendra; Wirawan, I Komang Arba (Capture : Jurnal Seni Media Rekam, 2019)
This research focuses on the actualization of women in the domestic area in the film Galuh. This film is an interesting study because the content in this film that contains local wisdom with the source of film ideas from marriage Pada Gelahang and also emphasizes the identity of conventional women with their domestic space. The formulation of the problem in the research is how the actualization of women in their domestic areas in the film Galuh. The purpose of this study is to study the actualization of women in their domestic territory in the film Galuh. This study uses descriptive qualitative research methods, with interpretive analysis. This research uses film’s elements such as narrative film and cinematic as well as ecofemism to present the spectrums that are seen in films that show women in quite different ways by complementing Galuh and which load more in the domestic area. The results of this study provide a specific understanding of Galuh through narrative and cinematic films that depict Galuh and her daughter as conventional and unconventional female characters with their domestic space.